SCREENING AND PROFILING OF PYTOCHEMICAL COMPOUNDS IN THE TEJA, BYADAGI AND US-341 CHILLI VARIETIES (The Review of Diabetic Studies, 2025)
Chilli (Capsicum annuum L.) is one of the most widely cultivated spice crops and holds significant importance due to its nutritional richness, pungency, and therapeutic potential. It contains a broad spectrum of bioactive compounds along with essential nutrients, including proteins, macro- and micro-minerals, and water-soluble vitamins. The characteristic heat of chilli is primarily attributed to capsaicin, an alkaloid responsible for its sensory and biological properties. In addition to its culinary relevance, chilli has been recognised for its role in supporting human health through antioxidant and metabolic functions.The present investigation was undertaken to comparatively evaluate the phytochemical constituents, physical characteristics, mineral composition, and vitamin profile of three commercially important chilli varieties, namely Teja, Byadagi, and US-341. Systematic screening and quantitative analyses were performed using standardised laboratory protocols to assess varietal differences. The outcomes of the study demonstrate significant variation among the selected varieties in terms of their biochemical composition and nutritional attributes. Each variety exhibited distinct characteristics that influence its suitability for food processing, nutritional enhancement, and market demand. These findings provide valuable insights for breeders, food technologists, and the nutraceutical industry, highlighting the importance of varietal selection in improving the nutritional quality and commercial utilisation of chilli.